Features of programming tasks optimization and organizational processes in construction through logistic methods - Аrutyunyan I.; Kovalenko М. (Ways to Improve Construction Efficiency, 2019)
In the article the features were considered when forming the conditions of tasks of optimization-organizational processes in the construction industry. The main types of economics and mathematical programming, namely, linear and non-linear programming, dynamic programming method are considered. Their disadvantages and advantages based on features of the construction industry. After analyzing, the author concludes that modern methods of solving problems of optimization-organizational processes by the method of dynamic programming does not reflect a complete picture of the costs when forming these tasks in construction.